Funções e suas aplicações - Melo, Deybson Oliveira (2015)
Due to the di culties related to introductory teaching of functions in primary and secondary education, we will make in this work, an approach about functions, emphasizing modeling, problem solving, and graphic building. In order to build the graph of the functions given in this paper, we introduce the concept of limits and derivatives focusing on the de nition of the tangent line to the graph of a function.